NurtureShock : new thinking about children - Bronson, Po, 1964-; Merryman, Ashley (New York : Twelve, 2009)
Award-winning science journalists Po Bronson and Ashley Merryman demonstrate that many of modern society's strategies for nurturing children are in fact backfiring--because key twists in the science of child development have been overlooked. The authors discuss the inverse power of praise, why insufficient sleep adversely affects kids' capacity to learn, why white parents don't talk about race, why kids lie, why evaluation methods for "giftedness" and accompanying programs don't work, and why siblings really fight.
The inverse power of praise -- The lost hour -- Why white parents don't talk about race -- Why kids lie -- The search for intelligent life in kindergarten -- The sibling effect -- The science of teen rebellion -- Can self-control be taught? -- Plays well with others -- Why Hannah talks and Alyssa doesn't -- The myth of the supertrait.
Includes bibliographical references (p. [265]-327) and index.
Keywords: Child development; Child psychology; Child rearing; Parenting